Analyzing the Students' Motivation towards the Use of ICT in Learning English - Febriyuliana Widyaningtyas; Farah Sukmawati Wahidah (Lembaga Penelitian (The Institute of Research) Universitas Swadaya Gunung Jati, 2021)
The present study aims to analyze the students' motivation towards the use of ICT in learning English. There are two types of motivation tested in this study: intrinsic and extrinsic. Intrinsic motivation includes self-efficacy and self-desire, while extrinsic motivation includes environmental factors and goals to be achieved. The participants in the present study are 33 eighth-semester university students from various departments in the Faculty of Teacher Training and Education, except English Education Department, from one private university in Cirebon, West Java, Indonesia, who got the English lessons as a subject taught in that university. The participants are from the Department of Economics Education, Mathematics Education, Elementary School Education, and Indonesian Language and Literature Education. The present study uses a qualitative case study method. The data is gathered from the distribution of online questionnaires and interviews. The questionnaire contains 18 questions and is divided into four parts: self-efficacy, self-desire, environmental factor, and goal to be achieved. Then, the writers conduct indirect interviews through one of the telecommunications applications, namely WhatsApp. The results indicated that intrinsic motivation was the motivation that most influenced non-English Department students' motivation to learn English using ICT. The most prominent intrinsic motivation was self-desire, where this motivation arose within oneself without being influenced by external or environmental factors.